The Role of Vocabulary Knowledge in Speaking Development of Saudi EFL Learners - Ishtiaq, Muhammad; Noor Raha, Mohd Radzuan; Shahbaz, Muhammad; Ainol Haryati, Ibrahim; Mustafa, Ghulam (AWEJ.org, 2018)
Speaking in a foreign language is considered to be a challenging aspect of language learning that demands competence and mastery in learning any foreign language. Vocabulary learning verifies to play an important role in oral communication. However, literature lacks the studies where both English as a foreign language (EFL) students and teachers’ views are obtained to provide analyses of the situations in which learners are not showing desired results in speaking. The current study explores the problems of lack of vocabulary that Saudi EFL students face with special focus on their speaking proficiency. It aims to seek EFL teachers’ opinions on the extent to which lack of vocabulary has influence on EFL students’ performance in listening, and conversation classes, and in expressing their ideas and feelings, and especially in speaking skill. A questionnaire was used for the responses from the students and an interview for the teachers to reveal their perceptions about the vocabulary hindrance in speaking skills. 20 EFL instructors and teachers of Preparatory Year Program (PYP) section of a public university and 110 EFL students participated in this study. The analysis of the data showed that both teachers and learners indicated that lack of vocabulary is one of the major factors in students’ inability to speaking English. In the current study, among many other suggestions it is proposed that the inclusion of mobile assisted language learning could be useful way of developing vocabulary for spoken proficiency of Saudi EFL learners.